Summary from Doctoral Dissertation Entitled: Problem of Limits of Rational Model of Human Actions. An Attempt to Capture Habitual-Rational Action - Ciesielski, Mieszko (Studia Europaea Gnesnensia, 2011)
Autoreferat z rozprawy doktorskiej pt. Zagadnienie ograniczeń racjonalnego modelu działań ludzkich. Próba ujęcia nawykowo-racjonalnego